我國專利法上均等論適用之實證研究：是變奏還是變調？ Empirical Study on the Doctrine of Equivalents in Taiwan - 張添榜 Tien-Pang Chang; 王立達 Richard Li-Dar Wang; 劉尚志 Shang-Jyh Liu (Kējì Fǎxué Pínglùn, 2013)
均等論（Doctrine of Equivalents）是決定專利侵權重要步驟之一，甚至被認為專利法中最重要的原則。實際上，由於其與專利公示作用的衝突，充滿不確定性，甚至被認為是專利法原則中，最困難且最不可預測的。當被控侵權技術超出申請專利範圍文義之外時，專利權人可依據均等論，對與專利均等之技術主張專利侵權。而判斷被控技術與專利均等的比對方式，目前我國司法實務，主要採取智慧財產局編訂之「專利侵害鑑定要點」，其中規範：若被控對象之構件，與對應申請專利範圍之要件，「係以實質相同的技術手段（Way），達成實質相同的功能（Function），而產生實質相同的結果（Result）時，則屬於該申請專利範圍要件之均等，兩者無實質差異。而所謂的實質相同，係指兩者之差異為該發明所屬技術領域中具有通常知識者所能輕易完成者。若比對之技術手段、功能、結果其中之一有實質不同，則不適用『均等論』。而此一比對手段、功能與結果的方式，一般稱為三步測試法」。然而，「專利侵害鑑定要點」對於如何適用三步測試法，並未有夠具體的說明。本文以智慧財產法院歷來判決作實證分析，並比對美國法，探討我國司法實務上對於三步測試法進一步的適用程序與規範，檢視其中的妥適性，並提出作者之觀察與建議。 The doctrine of equivalents is one of the most difficult and unpredictable doctrines in patent law to apply. By allowing patentees to gain exclusive right beyond the literal claims in their patents, this doctrine creates tension between the adequate protection of patent right and the public notice function in the patent system. Based on the Guideline for Patent Infringement Analysis proposed by Taiwan Intellectual Property Office, to determined patent infringement under the doctrine of equivalents, the Triple-Identity Test should be applied. Under this test, if an accused device performs substantially the same function in substantially the same way to obtain the same result as the asserted patent, the device infringes the patent. However, the information regarding the test is insufficient in the Guideline for Patent Infringement Analysis. It fails to explain how to apply the test, how to define the Way/Function/Result, and what the sequence of applying the three factors is. Without these detailed information, it will be desirable for the public to know how the Taiwan Intellectual Property Court apply the test. This article attempts to review the practice of the test by empirical study. Especially, this article surveys the patent infringement litigations in the Intellectual Property Court and tries to analyze the test implanted in the Court. Besides, this article also provides some comments and suggestions on the test in Taiwan.